Efektivitas konseling kelompok kognitif behavioral untuk meningkatkan kesadaran akademik mahasiswa - Masnurrima Heriansyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Academic quality improvement, self-development, and lecture completion can be realized if the students have academic awareness and are able to overcome various self-obstacles. This research aims to examine the effectiveness of cognitive-behavioral group counseling in increasing student academic awareness. The research type was the pre-experimental design of one group pre-test and post-test. The research sample was nine students under the guidance and counseling study program, Faculty of Teacher Training and Education, Mulawarman University. The analysis technique used was a descriptive analysis of percentages and the Wilcoxon test. The results showed that the student academic awareness increased based on the results of the pre-test and post-test as well as cognitive-behavioral group counseling was effective in increasing academic awareness after an effectiveness test was conducted.